How Learning Effectiveness of Taxation Courses and Tax Brevet Training Influence Career Choice in Taxation? - Resti Putri Kharisma; Usman Sastradipraja (Profesional Muda Cendekia Publishing, 2023)
Career choice in the field of taxation is one of the employment issues in the field of taxation. Therefore, the Minister of Finance issued several regulations trying to overcome these problems by carrying out various kinds of innovations. This study aims to determine the effect of the effectiveness of learning tax courses and tax brevet training on career choices in taxation. The type of research used is quantitative. The number of samples in this study were 100 respondents, namely students and alumni who were enrolled in the accounting study program at the Unjani Faculty of Economics and Business. Data collection used a questionnaire and was processed using SPSS 25. The results in this study show that partially the effectiveness of learning tax courses has a positive and significant effect on career choices in taxation, tax brevet training partially has no positive and significant effect on career choices in taxation. Simultaneously the variable effectiveness of learning taxation courses and tax brevet training influences career choices in the field of taxation